Progesterone Prolongs Viability and Anti-inflammatory Functions of Explanted Preterm Ovine Amniotic Membrane - Canciello, Angelo; Teti, Gabriella; Mazzotti, Eleonora; Falconi, Mirella; Russo, Valentina; Giordano, Antonio; Barboni, Barbara (Frontiers in Bioengineering and Biotechnology, 2020)
Amniotic membrane (AM) is considered an important medical device with many applications in regenerative medicine. The therapeutic properties of AM are due to its resistant extracellular matrix and to the large number of bioactive molecules released by its cells. An important goal that still remains to be achieved, is the identification of cultural and preservation protocols able to maintain in time the membrane morphology and the biological properties of its cells. Recently, our research group demonstrated that progesterone (P4) is crucial in preventing the loss of epithelial phenotype of amniotic epithelial cells in vitro. Followed by this premise, it has been evaluated whether P4 may also affect AM properties in a short-term culture. Results confirm that P4 preserves AM integrity and architecture respect to untreated AM which showed alterations in morphology. TEM analyses demonstrate that P4 also maintains unaltered cell-cell junctions, nuclear status and intracellular organelles. On the contrary, untreated AM experienced an extensive cell death and a strong reduction of immunomodulatory properties, measured in terms of anti-inflammatory cytokines expression and secretion. Overall, these results could open to new strategies to ameliorate the protocols for cryopreservation and tissue culture which represent preliminary stages of AM application in regenerative medicine.